Medical Evidence and Expertise in Abortion Jurisprudence. Issue 1 (March 2015) - Ahmed, Aziza
For another thing, the division of medical opinion about the matter at most means uncertainty, a factor that signals the presence of risk, not its absence. That division here involves highly qualified knowledgeable experts on both sides of the issue.— Stenberg v. Carhart, 2000 1 While we find no reliable data to measure the phenomenon, it seems unexceptionable to conclude some women come to regret their choice to abort the infant life they once created and sustained.— Gonzales v. Carhart, 2007 2